2021
DOI: 10.3389/fmicb.2020.618097
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Fast SARS-CoV-2 IgG ELISA, Based on Receptor-Binding Domain, and Its Comparative Evaluation Using Temporally Segregated Samples From RT-PCR Positive Individuals

Abstract: SARS-CoV-2 antibody detection assays are crucial for gathering seroepidemiological information and monitoring the sustainability of antibody response against the virus. The SARS-CoV-2 Spike protein’s receptor-binding domain (RBD) is a very specific target for anti-SARS-CoV-2 antibodies detection. Moreover, many neutralizing antibodies are mapped to this domain, linking antibody response to RBD with neutralizing potential. Detection of IgG antibodies, rather than IgM or total antibodies, against RBD is likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 34 publications
2
26
0
1
Order By: Relevance
“…Anti-SARS-CoV-2 RBD IgG antibody was detected using an ELISA as described previously. 5 Briefly, samples and controls were diluted to 1:50 in the sample diluent, and 100 μL was added per well of the stabilized RBD-coated plate. After 30 minutes of incubation at room temperature (23 ± 2°C), the plates were washed six times with wash buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Anti-SARS-CoV-2 RBD IgG antibody was detected using an ELISA as described previously. 5 Briefly, samples and controls were diluted to 1:50 in the sample diluent, and 100 μL was added per well of the stabilized RBD-coated plate. After 30 minutes of incubation at room temperature (23 ± 2°C), the plates were washed six times with wash buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies showed that S protein-based ELISA test was less sensitive to detect IgG and IgA against SARS-CoV-2 (<70%) [206] , [207] while few other studies reported that such test was highly sensitive (at least 90%) to detect IgG, IgA, or IgM against the virus S antigen [199] , [204] , [205] , [208] . Therefore, N protein-based ELISA assay could be a better choice of ELISA test to predict serological response in the SARS-CoV-2 patients as the test results of this assay seem to be more consistent and vary less in different reported studies [202] , [203] as compared to the S protein-based ELISA test [199] , [204] , [206] , [207] , [208] , [209] . On the other hand, some studies had reported the use of ELISA test that was aimed to detect different antibodies against different proteins of SARS-CoV-2, and examples of these tests were tests that were focusing to detect antibodies against N and S protein of SARS-CoV-2 [196] , [204] , [209] , [210] , [211] , [212] , [213] , [214] , [215] .…”
Section: Different Diagnostic Approaches To Detect Mers-cov and Sars-cov-2 Infectionsmentioning
confidence: 99%
“…Therefore, N protein-based ELISA assay could be a better choice of ELISA test to predict serological response in the SARS-CoV-2 patients as the test results of this assay seem to be more consistent and vary less in different reported studies [202] , [203] as compared to the S protein-based ELISA test [199] , [204] , [206] , [207] , [208] , [209] . On the other hand, some studies had reported the use of ELISA test that was aimed to detect different antibodies against different proteins of SARS-CoV-2, and examples of these tests were tests that were focusing to detect antibodies against N and S protein of SARS-CoV-2 [196] , [204] , [209] , [210] , [211] , [212] , [213] , [214] , [215] . Compared to molecular detection using the qRT-PCR method that showed more consistent test sensitivity and specificity across different reported studies as an example [71] , [72] , [87] , [88] , the sensitivity and specificity of ELISA assays in detecting various antibodies (IgG, IgA, and IgM) against different antigen proteins of SARS-CoV-2 demonstrated a high degree of variations in which some studies reported low test sensitivity (<60%) [183] , [196] , [216] and specificity (as low as below 80%) [215] whereas some studies would report high test sensitivity and specificity (>85%) [210] , [211] .…”
Section: Different Diagnostic Approaches To Detect Mers-cov and Sars-cov-2 Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The uniqueness of RBD region among the coronavirus families, makes the anti-RBD IgG specific to each species. Hence the antibodies against RBD possess more neutralizing effect on the virus and are considered to be the most suitable antibody for the assessment of immunity against COVID-19 [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%